A BRCA1 promoter variant (rs11655505) and breast cancer risk. Issue 4 (22nd April 2010) - Verderio, Paolo; Pizzamiglio, Sara; Southey, Melissa C; Spurdle, Amanda B; Hopper, John L; Chen, Xiaoqing; Beesley, Jonathan; kConFab; Schmutzler, Rita K; Engel, Christoph; Burwinkel, Barbara; et al.
Abstract : Background: A study of Chinese women recently suggested that the minor allele of rs11655505 in the BRCA1 promoter (c.–2265C→T) increases promoter activity and has a protective effect on breast cancer risk. Methods: We genotyped rs11655505 in 2912 female breast cancer cases and 2783 unaffected female controls from four Caucasian breast cancer studies. Results: No evidence for an association between rs11655505 and breast cancer risk was found. Conclusions: Our study failed to confirm a role of rs11655505 in breast cancer risk. Larger studies are necessary to determine if there is a weak association between this SNP and breast cancer risk.